Juventude e políticas públicas no Brasil - Marilia Sposito Pontes; Paulo César Carrano Rodrigues (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2003)
The article endeavours to outline a wide-ranging understanding of the paths explored in the last ten years by those initiatives focused on the juvenile segments of Brazilian society. Based upon a democratic conception of attainment of public policy and on a clear defence of young people as subjects with their own rights, it begins an analysis of policies for youth. To that end, based on some theoretical considerations on the theme of youth, particularly concerning its breadth, it examines the federal actions proposed during the period 1995-2002 and traces some of the paths explored at the municipal level aimed at establishing such policies.